MAKNA LAGU YAA LAL WATHAN DALAM MENGKONSTRUKSI JIWA NASIONALISME SISWA MI NU HIDAYATUN NAJAH TUBAN - Fahrudi, Emi; Mundzir, Moh. (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
Character Education for the next generation is a mandatory thing that must be considered seriously. It has become our responsibility to instilled nationalism character on young generation since elementary school age. The development of technology that influences lifestyle and family parenting models also contributes to the growth and development of nationalism construction in children which is increasingly eroded. Responding to this phenomenon, educational institutions become the second pillar after the family to design and construct children's nationalism. In this case, the Ma'arif NU educational institution designed a character education program to construct nationalism and a sense of love for the country through a mandatory program, namely singing the song “Yaa lal wathon” at every activity, both official and ceremonial, and making this song the second mandatory song after the song Indonesia Raya. In practice, this song has become a routine that makes students continue to sing the song. In this study, the researcher aims to reveal: (1) How is the interpretation of the meaning of the song